Autonomy Lost: the Bureaucratization of Higher Education - Clare, Julia; Sivil, Richard (South African Journal of Higher Education, 2016)
Transformation of the higher education sector in post-1994 South Africa serves a dual purpose. Firstly, it is a response to the local imperative of democratization, in the sense of developing citizenship and social redress. Secondly, it is an attempt to reposition South African universities within the global higher education terrain, which had changed considerably during the preceding period of South Africa’s isolation. The scale of these changes has understandably caused feelings of discontent among academics, and has resulted in a growing literature, which seeks to explain both the process of transformation and its effects in terms of corporatization. We argue instead that transformation of higher education is better understood as a process of bureaucratization. We acknowledge that this bureaucratization has corporate aspects, but argue that these are incidental rather than essential. What is essential is the importation and imposition of an administrative structure which has brought academics increasingly under surveillance. This has not only changed the nature of the job, but also the ways in which academics relate to themselves and others, and has significantly eroded the autonomy of individual academics. We end by considering a range of responses to attend to this loss of autonomy.